Wilms' tumor 1 mRNA expression: a good tool for differentiating between myelodysplastic syndrome and aplastic anemia in children?. Issue 1 (1st January 2019) - Zuo, Yingxi; Cheng, Yifei; Zhang, Leping; Qin, Yazhen; Luo, Hong
ABSTRACT: Objectives: To evaluate the value of Wilms' tumor 1 mRNA ( WT1 ) expression in the differential diagnosis of childhood myelodysplastic syndrome (MDS) and aplastic anemia (AA). Methods: This study compared WT1 expression levels in children of MDS and AA to evaluate its value in differential diagnosis. Results: WT1 overexpression rate and mean WT1 expression level were significantly higher in MDS compared to AA ( P  = 0.000 and P  = 0.013, respectively). Patients with RCC and normal cytogenetics exhibited significantly greater portion of patients exposing WT1 overexpression, compared to all AA subtypes ( P = 0.001, P = 0.000 and P = 0.001, respectively). ROC curve analysis revealed that WT1 expression could differentiate between RCC with normal cytogenetics and non-severe AA. Based on a cut-off value of 1.45%, WT1 expression provided a sensitivity of 23.2% and a specificity of 100%. Discussion: In the present study, WT1 overexpression rate was gradually decreased in RAEB group, RCC group and AA subtypes, and the mean WT1 expression level of the MDS patients was significantly higher than that of the AA group. It is very difficult to differentiate between RCC with normal cytogenetics and NSAA in children. Our results showed significant differences in WT1 overexpression rate between these two groups. When we set the cut-off value as 1.45%, WT1 expression levels could be used to differentiate between cases of RCC with normal cytogenetics and NSAA in children. Conclusion: WT1 expression might be useful for distinguishing between myelodysplastic syndrome and aplastic anemia in children.